The Victories of Merenptah, and the Nature of their Record - Kitchen, Kenneth (Journal for the study of the Old Testament, 2004)
This article responds to that by I. Hjelm and T.L. Thompson (‘The Victory Song of Merenptah, Israel and the People of Palestine’, JSOT 27.1 [2002], pp. 3-18), concerning the nature of the war-inscriptions of Merenptah of Egypt, and especially of the role of his triumph-hymn and the significance of the mention of Israel in that document, in pointing out standard Egyptian usage of the New-Kingdom period (sixteenth-twelfth centuries BCE) to which Merenptah’s texts conform, and correcting misunderstandings of these data by Hjelm and Thompson and some of their precursors.